Women in Agriculture: Accelerating Impact of CGIAR Climate Research for Africa - Kyalusanza, Mukumbi; Bohjanen, Carey; Sika, Gbegbelegbe; Chikoye, David; Jacobs-Mata, Inga (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
The objective of this workshop was to deep dive into a collaborative approach to identifying potential solutions, consider the role of key ecosystem stakeholders including the banks, policy makers and IITA/AICCRA and prioritise wish list items for potential action. The conclusions reached provide a framing and context for next steps of stakeholder engagement in the third and final workshop for this phase of work.